Hubungan persepsi anak mengenai dukungan sosial orangtua terhadap perilaku mengkonsumsi buah - Anindia, Mina Henrietty; Fourianalistyawati, Endang (Konsorsium Psikologi Ilmiah Nusantara, 2013)
This research was conducted based on the phenomenon where children are more familiar with foods that have a low nutrient content. Fruit is a healthy food intake component that has many beneits. Child feeding behavior relate to the role of parents in providing social support, including the support provided in the form of emotional support, self-esteem, instrumental, informational, and social networking. Attitude is the evaluation of various aspects of the social world that includes the people around, objects, and ideas. Attitudes are formed from the components of affective, cognitive, and behavioral. All three components must be consistent with one another, so that alignment occurs in the formation of attitudes. Children have the ability to see and judge others, it is called social perception. A total of 70 elementary school students ranging in age from 9-11 years participated in the study. Children with the age range has been progressing more advanced cognitively and socially. In this study, the scale of the study was made by researchers. The results showed that there was a signiicant relationship between children’s perception of the social support parents with children’s attitudes towards the consumption of fruit. Thus, it was suggested to the parties concernedto participate to make efforts to increase consumption of fruit in children, as a way to maintain health.